Comprehensive mutant chemotyping reveals embedding of a lineage-specific biosynthetic gene cluster in wider plant metabolism - Xue Qiao; Alan Houghton; James Reed; Burkhard Steuernagel; Jiahe Zhang; Charlotte Owen; Aymeric Leveau; Anastasia Orme; Thomas Louveau; Rachel Melton; Brande B. H. Wulff; Anne Osbourn (Proceedings of the National Academy of Sciences, 2025)
Plants produce diverse specialized metabolites with important ecological functions. It has recently become apparent that the genes for many of these pathways are not dispersed in plant genomes, but rather are arranged like beads on a string in biosynthetic gene clusters (BGCs). Pathways encoded by BGCs are as a rule dedicated linear pathways that do not form parts of wider metabolic networks. In contrast, the genes for the biosynthesis of widely distributed more ancestral metabolites such as carotenoids and anthocyanins are not clustered. Little is known about how these more recently evolved clustered pathways interact with general plant metabolism. We recently characterized a 12-gene BGC for the biosynthesis of the antimicrobial defense compound avenacin A-1, a triterpene glycoside produced by oats. Avenacin A-1 is acylated with the fluorophore N -methyl anthranilate and confers bright blue fluorescence of oat root tips under ultraviolet light. Here, we exploit a suite of >100 avenacin-deficient mutants identified by screening for reduced root fluorescence to identify genes required for the function of this paradigm BGC. Using a combination of mutant chemotyping, biochemical and molecular analysis, and genome resequencing, we identify two nonclustered genes ( Sad4 and Pal2 ) encoding enzymes that synthesize the donors required for avenacin glycosylation and acylation (recruited from the phenylpropanoid and tryptophan pathways). Our finding of these Cluster Auxiliary Enzymes (CAEs) provides insights into the interplay between general plant metabolism and a newly evolved lineage-specific BGC.